Therapeutic journeys working with complex clients : unravelling the chaos - Helfgott, Sue; Narayanan, Shireen; Sushi Productions; Instructional Resources Productions (Australia : Sushi Productions, 2006)
In this interviews with her clients, the counsellor explores a number of presenting problems including the client's anxiety, her drug use, the risk of harm to her childdren, a suicide risk assessment, relationship difficulties, financial problems and past child sexual abuse
Title from title screen
DVD format
Keywords: Counseling; Alcoholism counseling; Counselor and client